Análise através do método dos elementos finitos das tensões desenvolvidas no reborbo alveolar sob as próteses totais com três diferentes conceitos oclusais - Ferreira, Luciano Pedrin Carvalho [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The strain distribution patterns in the alveolar residual ridge as a consequence of occlusal loads applied in complete dentures constructed with different occlusal schemes are not known. The aim of this study was to develop a comparative and qualitative analysis of the strains generated in the right first molar region of the supporting structures of a mandibular complete denture using the two-dimentional Finite Element Analysis (FEA-2D). Coronal section two-dimensional models were developed reflecting mandibular complete dentures constructed with three different schemes of occlusion, namely conventional (CO), Lingualized (LO) and monoplane (PO). The models also had variations in the contour of the supporting structures, representing four conditions of residual ridge resorption: (1) high, well rounded; (2) knife edge; (3) low, well rounded, and (4) depressed. Two materials of artificial teeth were considered: acrylic resin and porcelain. A vertical load of 50 N was applied onto the occlusal surface of the mandibular right first molar. The software GID (International Center for Numerical Methods in Engineering, Barcelona, Spain) generated images of Von Mises (stress) and vertical (compression or tensile) strains in the FEA-2D models. Within the limitations of this study the following conclusions were drawn: (1) Stress and compression were observed in the supporting structures with all of the studied occlusal schemes; (2) The distribution of stress and compression with CO dentures generated patterns of intensity with the appearance of horizontal layers and, with LO and PO dentures with the appearance of vertical layers; (3) With CO dentures the intensity of stress and compression increased progressively from the crest of the residual ridge to the alveolar bone and, with LO and PO dentures from the buccal to the lingual slope of the ridge; (4) With all of the studied occlusal schemes, neither the...

A distribuição das tensões nas estruturas de suporte de tensões decorrentes de forças oclusais aplicadas a próteses totais confeccionadas com diferentes esquemas oclusais não são conhecidos. O objetivo deste estudo foi desenvolver, através do método de elementos finitos bidimensional (MEF-2D), uma analise comparativa e qualitativa das tensões geradas nas estruturas de suporte na região de primeiro molar inferior direito de próteses totais confeccionadas com: (1) Oclusão convencional (OC); (2) Oclusão lingualizada (OL) e, (3) Oclusão monoplana (OP). Os padrões de distribuição de tensões foram observados em quatro condições de reabsorção óssea do rebordo alveolar: (1) alto e convexo; (2) lamina de faca; (3) baixo e convexo e, (4) involuido. Dois materiais de confecção de dentes artificiais foram considerados: resina acrílica e porcelana. Modelos digitais bidimensionais para a aplicação do MEF-2D foram desenvolvidos para as condições propostas. Uma carga vertical de 50N foi aplicada na superfície oclusal do primeiro molar inferior direito. Através do software GID (International Center for Numerical Methods in Engineering, Barcelona, Espanha) foram geradas imagens gráficas de stress (tensões de Von Mises) e de compressão (tensões verticais) nas estruturas de suporte. Neste estudo concluiu-se que: 1. Todos os esquemas oclusais estudados transmitiram stress e compressão para as estruturas de suporte; 2. 15 OC gerou um padrão de distribuição de stress e de compressão em faixas horizontalizadas, enquanto que OL e OP em faixas verticalizadas; 3. OC apresentou um padrão de distribuição de intensidade de stress e de compressão que aumenta da crista do rebordo alveolar para o osso esponjoso, enquanto que OL e OP um padrão que aumenta de vestibular para lingual; 4. Os diferentes níveis de reabsorção do rebordo não interferiram nas intensidades ou padrões...
Keywords: Prótese total; Oclusão (Odontologia); Reabsorção óssea; Denture complete; Dental occlusion; Bone resorption